Arthroscopic Synovectomy Combined with Autologous Fat Grafting in Early Stages of CMC Osteoarthritis of the Thumb - Kemper, Robert; Wirth, Johanna; Baur, Eva-Maria (Journal of Wrist Surgery, 2018)
Background Minimal invasive treatments such as arthroscopic techniques may be adequate to restore the anatomy and functional integrity of the thumb CMC (carpometacarpal) joint. In this paper, we reported the interposition of autologous fat tissue in combination with arthroscopic synovectomy/debridement for early stage of the thumb CMC joint osteoarthritis. Patients and Methods Twelve patients with a mean age of 46 years with early radiological stages of thumb CMC joint osteoarthritis were included. Evaluation of outcome was measured prior and 3, 12, and 24 months after surgery including, Visual Analog Scale (VAS), QuickDASH, grip and pinch strength, range of motion (ROM), and patient satisfaction.Results Pain at rest (or with load) was reduced from preoperative 4,7 (8,7) to 2 (5,9) at 3 to 6 months; 1,4 (4,3) at 12 months; and 0,75 (2,7) at 2 years after the surgery. Initial preoperative QuickDASH value of 52 points reduced to 33 (17–65) at 6 months, 23 (2–70) at 12 months, and 20 (11–29) at 24 months after the surgery. Grip strength and thumb pinch with respect to the contralateral untreated thumb was reduced in the first 12 months but recovered subsequently. ROM was equal to the contralateral thumb. Three patients suffered from tendinitis and required surgical treatment. One patient indicated prolonged pain symptoms. No infections were noted and no donor-site morbidity or side effects were detected. Conclusion Arthroscopic synovectomy combined with autologous fat graft is a reliable surgical option for early thumb CMC joint osteoarthritis and that effect continues for more than 24 months.
Keywords: autologous fat graft; carpometacarpal joint osteoarthrosis; basilar thumb osteoarthrosis; minimal invasive treatment; small joint arthroscopy; osteoarthrosis